Yield performance, mineral profile, and nitrate content in a selection of seventeen microgreen species - Di Gioia, Francesco; Hong, Jason C.; Pisani, Cristina; Petropoulos, Spyridon A.; Bai, Jihne; Rosskopf, Erin N. (Frontiers in Plant Science, 2023)
Originally regarded as garnish greens, microgreens are increasingly valued for their nutritional profile, including their mineral content. A study was conducted under controlled environmental conditions utilizing a selection of seventeen microgreen species belonging to seven different botanical families to investigate the genetic variation of macro- and micro-minerals and nitrate (NO3-) content. Plants were grown in a soilless system using a natural fiber mat as the substrate. After germination, microgreens were fertigated with a modified half-strength Hoagland solution prepared using deionized water and without adding microelements. At harvest (10 to 19 days after sowing, based on the species), yield components were measured and dry tissue samples were analyzed for the concentration of total nitrogen (N), NO3-, P, K, Ca, Mg, S, Na, Fe, Zn, Mn, Cu, and B. Genotypic variations were observed for all of the examined parameters. Nitrogen and K were the principal macronutrients accounting for 38.4% and 33.8% of the total macro-minerals concentration, respectively, followed in order by Ca, P, S, and Mg. Except for sunflower (Helianthus annuus L.), all the tested species accumulated high (1,000-2,500 mg kg-1 FW) or very high (>2,500 mg kg-1 FW) NO3- levels. Eight of the studied species had a K concentration above 300 mg 100 g-1 FW and could be considered as a good dietary source of K. On the other hand, scallion (Allium fistulosum L.), red cabbage (Brassica oleracea L. var. capitata), amaranth (Amaranthus tricolor L.), and Genovese basil (Ocinum basilicum L.) microgreens were a good source of Ca. Among micro-minerals, the most abundant was Fe followed by Zn, Mn, B, and Cu. Sunflower, scallion, and shiso (Perilla frutescens (L.) Britton) were a good source of Cu. Moreover, sunflower was a good source of Zn, whereas none of the other species examined could be considered a good source of Fe and Zn, suggesting that supplementary fertilization may be required to biofortify microgreens with essential microminerals. In conclusion, the tested microgreens can be a good source of minerals showing a high potential to address different dietary needs; however, their yield potential and mineral profile are largely determined by the genotype.